2021
DOI: 10.3390/su13031021
|View full text |Cite
|
Sign up to set email alerts
|

From Barriers to Enablers: The Role of Organizational Learning in Transitioning SMEs into the Circular Economy

Abstract: To contribute to small and medium enterprises’ (SMEs) sustainable transition into the circular economy, the study proposes the activation of organizational learning (OL) processes—denoted here as multi-level knowledge creation, transfer, and retention processes—as a key phase in introducing circular business models (CBMs) at SME and supply chain (SC) level. The research employs a mixed-method approach, using the focus group methodology to identify contextual elements impacting on CBM-related OL processes, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…Self-financing, debt financing, and public funds have proven to be the causes of the practice of CE-based business models from a financial perspective in general in SMEs. Scipioni et al (2021) argued that the critical factors of a CE-based business model for the MSME construction sector in Italy are external stakeholders, supply chain stakeholders, and organizational culture. In addition, barriers to and enablers for OL processes related to the CE-based business model from a knowledge perspective (creation, transfer, and retention) are found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-financing, debt financing, and public funds have proven to be the causes of the practice of CE-based business models from a financial perspective in general in SMEs. Scipioni et al (2021) argued that the critical factors of a CE-based business model for the MSME construction sector in Italy are external stakeholders, supply chain stakeholders, and organizational culture. In addition, barriers to and enablers for OL processes related to the CE-based business model from a knowledge perspective (creation, transfer, and retention) are found.…”
Section: Resultsmentioning
confidence: 99%
“…The innovations in MSME that they do incrementally in resource loops will consider profits, costs, knowledge, experts, supply, and demand-side; and externally requires government supports such as regulations, standards, and infrastructure; as listed in table 4. Only Scipioni et al (2021) gives rise to a user behavior/market context, while others focus heavily on the operational parts of the business model. Research by Bocken & Geradts (2022), through interviews with 200 managers of leading corporations related to sustainability, found three critical things: market desirability, technical feasibility, and business viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to operationalize the implementation of the concept of sustainable development for businesses, the Circular Economy (CE) concept has received increasing attention worldwide and has become an important field to both scholars and practitioners with a large increase in the number of articles and journals covering the topic during the last years (e.g., [18][19][20]). Although there is no generally accepted definition for the concept of Circular Economy, Kirchherr et al [19] describe it as "an economic system that is based on business models which replace the 'end-of-life' concept with reducing, alternatively reusing, recycling and recovering materials in production/distribution and consumption processes with the aim to accomplish sustainable development, which implies creating environmental quality, economic prosperity and social equity, to the benefit of current and future generations".…”
Section: Sustainabilitymentioning
confidence: 99%
“…Another survey-based analysis of 76 companies indicated that significant initial funding costs, as well as a misunderstanding and sense of urgency, are the main CE adoption barriers at the focal-firm level [53]. Moreover, Scipioni et al [54] categorized barriers into those that are internal versus external to the focal firm, and they suggested modes of circular business models that require tailor-made CE solutions.…”
Section: Ce Implementationmentioning
confidence: 99%